Sandman, récit métamorphe : l’espace du chapitre chez Neil Gaiman - Raphaël Luis (Itinéraires)
This paper focuses on the chaptering of Neil Gaiman’s comic book Sandman (1989-1996) through the dialectic between DC Comics’ editorial constraints and the aesthetic flexibility of the graphic novel. We highlight that these two opposite trends lead to a complex architecture whose primary objective is to incorporate every literary genre in a new space, midway between popular production and metaxtual commentary.